Analysis of The Potential of Superior Food Crop Commodities in Siak Regency with Geographic Information System (GIS) Visualization - Zargustin, Dedi; Harmaidi, Desma; Siswati, Latifa; Nizar, Rini (Jurnal AGRISEP, 2026)
Regional economic development, in rural areas, relies heavily on the identification of key sectors with the highest growth potential. In this context, the agricultural sector, especially food crop production, is the backbone of local economic resilience. The development of superior food crop commodities in Siak Regency is very important to increase agricultural productivity and the welfare of rural communities. To assess this potential, the study integrated several analysis methods, including the Sectoral Contribution Index (SCI), Growth Ratio Model (GRM), Location Quotient (LQ), and Dynamic Location Quotient (DLQ), which were combined in the Composite Index (CI). In addition, GIS is used to visualize the spatial distribution of these analyses. The results showed that Bungaraya Village and Kemuning Muda Village were the main contributors to rice production in Siak Regency, each accounting for 23% of the total rice production in the area. GRM analysis shows that Temusai Village has the highest growth rate of rice production, even though it is influenced by external factors that cause production fluctuations. The results of the LQ and DLQ analysis show that some villages, such as Bungaraya and Kemuning Muda, not only meet local needs but also have the potential to support exports. The use of GIS to visualize the results of this analysis allows mapping of the spatial distribution and identification of areas with potential for further development. These findings are expected to be the basis for policy-making that supports the development of sustainable agriculture and the improvement of community welfare in Siak Regency.